Analysis of the Influence of Local Revenue Balancing Fund and Gross Regional Domestic Product on the Human Development Index in West Nusa Tenggara Province in 2008-2022 - Satria Molandy Putra; Abdul Manan; Titi Yuniarti (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This study aims to analyze the effect of Regional Original Revenue, Balance Fund and Gross Regional Domestic Product on the Human Development Index in West Nusa Tenggara Province. This type of research is descriptive research with a quantitative approach, the type of data used in this study is quantitative data and secondary data in the form of time series and cross section data in the form of annual data during 2008-2022 for 15 years. The collection technique used in this research is the documentation method. From the results of partial and simultaneous testing, it shows that Regional Original Revenue, Balance Funds and Gross Regional Domestic Product have a significant effect on the Human Development Index in West Nusa Tenggara Province.